Analisis Konsentrasi dan Karakteristik Mikroplastik di Kawasan Wisata Pantai Congot Desa Jangkaran Kabupaten Kulon Progo - Bela Agustina Eka Putri Kusniati; Trisno Fallo; Muhammad Noviansyah Aridito; Andri Prasetyo Nugroho; Putri Ratna Setyowati (Proklamasi 45 University, 2025)
Congot Beach is a tourist area that is also inhabited by many fishermen. The issue of plastic waste on this beach is quite serious, with a large amount of waste being discarded by visitors, local residents, and fishermen. Additionally, Congot Beach is located near the estuary of the Bogowonto River, which serves as a major pathway for microplastics entering the ocean. This study aims to analyze the concentration and characteristics of microplastics in the Congot Beach Tourist Area, Jangkaran Village, Kulon Progo Regency. This research employs microscopy and Fourier-transform infrared spectroscopy (FTIR) methods to identify the concentration, shape, color, and polymer types of microplastics found at the study site. The study results indicate that the range of microplastic concentrations at Congot Beach, Kulon Progo, based on calculations from NOAA, sensitivity studies, and mean values, is 1672 particles/L (Negative Study) – 2090 particles/L (Mean) – 2508 particles/L (Positive Study). These results are categorized as an emergency pollution level according to the Guidelines for the Monitoring and Assessment of Plastic Litter in the Ocean (GESAMP). The characteristics of the microplastics found include fragment shapes (53.3%), film (31.8%), fiber (11.2%), and pellet (3.6%). The dominant colors of the microplastics are transparent (34.4%), green (26.6%), and black (25.8%). The identified polymer types of microplastics are High-Density Polyethylene (HDPE) and Polypropylene (PP).